Late Ordovician lingulid brachiopods from the Pingliang Formation (Shaanxi Province, North China): Morphological and ecological implications - Liang, Yue; Fu, Rao; Hu, Yazhou; Liu, Fan; Song, Baopeng; Luo, Mei; Ren, Xinyi; Wang, Jiayue; Zhang, Caibin; Fang, Ruisen; Yang, Xuan; Holmer, Lars E.; et al. (Journal of Asian earth sciences, 2024)
•Lingulid brachiopod Anomaloglossa porca from the Late Ordovician of North China.•Paleogeographic distribution has extended from Gondwana and Tarim to North China.•Geometric morphometric analysis indicates an infaunal lifestyle of this taxon. Brachiopods first appeared in the early Cambrian and persist till present. They are one of the main lineages of marine invertebrates that diversified throughout the Paleozoic and reached their maximum diversity of high-rank taxonomy during the Ordovician. During this time interval, brachiopods were mainly dominated by the articulated Orthida and Strophomenida, which represent major components of the Paleozoic Evolutionary Fauna; however, the inarticulated lingulid brachiopods (Order Lingulida) were comparatively less abundant and received less attention during this time period. Here, we report a new record of the lingulid brachiopod Anomaloglossa porca from the Upper Ordovician (Sandbian) Pingliang Formation of the Xilinggou Section, Shaanxi Province, North China. Collected specimens are preserved as calcium phosphatic shells with highly mineralization which preserve detailed morphology and shell ornamentation of both ventral and dorsal valves. The new occurrence of A. porca extends its paleogeographic distribution from Gondwana and Tarim to North China Platform. Moreover, comprehensive geometric morphometric analysis of A. porca is performed and the results indicate that both the shell shape and pseudointerarea are very close to the recent infaunal lingulids. If interpreted correctly, the fossils represent the first example of infaunal lifestyles achieved by Ordovician lingulids from North China, exhibiting the ecological complexities of the Late Ordovician benthos composed of epibenthos and infaunas as well.